Instagram and YouTube, Visual Culture and University Education : A Systematic Review - Peña-Acuña, Beatriz; Alfonso Jaramillo, Francisco (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
In the technological age, higher education is at a crossroads that requires a redefinition of pedagogical paradigms. The analysis focuses on the integration of Instagram and YouTube as pedagogical tools for visual culture. The convergence of visual culture and social media poses challenges in the face of media saturation. The systematic review underpins the transformative potential of these platforms in higher education. Continuous teacher training and innovative pedagogical strategies are essential to optimise their impact. Envisioning the classroom as a space where visual culture and active methods converge opens up a promising pedagogical horizon for higher education.